Con-donare. Ipertrofia del dono nello Sri Lanka post-tsunami - Mara Benadusi (EtnoAntropologia)
The paper traces a biography of the gift in post-tsunami Sri Lanka. It shows that the process of “commodification” of international aid was not produced by a monolithic humanitarian apparatus, considered as the perverse expression of the interference of the North on the South of the world. Various ethnographic studies prove that the “competitive humanitarianism” that emerged in Sri Lanka resulted by an interrelate network of individuals and organizations which overcomes the rigid distinction between beneficiaries and donors, expatriates and locals, experts and non-experts.